IMPLIKASI JUDI ONLINE TERHADAP MORALITAS DAN EKONOMI UMAT: TINJAUAN HUKUM ISLAM - Siti Nurharirah; Irmayanti Kumara Tungga; Miliyanti; Syarifah Raehana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The$ rapid advance$ me$ nt of digital te$ chnology has contribu$ te$ d to the$ wide$ spre$ ad Pre$ vale$ nce$ of online$ gambling across variou$ s le$ ve$ ls of socie$ ty. This Phe$ nome$ non not only cau$ se$ s significant financial losse$ s bu$ t also u$ nde$ rmine$ s The$ moral and spiritu$ al fou$ ndations of the$ Mu$ slim commu$ nity. This stu$ dy Aims to e$ xamine$ the$ implications of online$ gambling on morality and the$ E$ conomic we$ ll-be$ ing of the$ u$ mmah from the$ pe$ rspe$ ctive$ of Islamic law. The$ Re$ se$ arch adopts a qu$ alitative$ approach u$ sing library re$ se$ arch me$ thods, Focu$ sing on normative$ analysis of re$ le$ vant ve$ rse$ s of the$ Qu$ r’an, Hadiths, And classical as we$ ll as conte$ mporary Islamic le$ gal and e$ conomic lite$ ratu$ re$ . The$ findings indicate$ that online$ gambling falls u$ nde$ r the$ cate$ gory of almaisir, which is strictly prohibite$ d in Islam du$ e$ to its e$ le$ me$ nts of u$ nce$ rtainty (gharar), e$ xploitation, and harm to othe$ rs. Fu$ rthe$ rmore$ , online$ gambling Contribu$ te$ s to the$ de$ gradation of individu$ al morality, worse$ ns hou$ se$ hold Financial conditions, and can le$ ad to stru$ ctu$ ral pove$ rty. The$ re$ fore$ , e$ ffe$ ctive$ pre$ ve$ ntion and mitigation e$ fforts are$ e$ sse$ ntial and shou$ ld be$ imple$ me$ nte$ d throu$ gh le$ gal e$ nforce$ me$ nt, moral e$ du$ cation, and the$ stre$ ngthe$ ning of family and commu$ nity role$ s.